Does sumatriptan cross the blood–brain barrier in animals and man? - Tfelt-Hansen, Peer Carsten (Springer Milan, 2009)
Sumatriptan, a relatively hydrophilic triptan, based on several animal studies has been regarded to be unable to cross the blood–brain barrier (BBB). In more recent animal studies there are strong indications that sumatriptan to some extent can cross the BBB. The CNS adverse events of sumatriptan in migraine patients and normal volunteers also indicate a more general effect of sumatriptan on CNS indicating that the drug can cross the BBB in man. It has been discussed whether a defect in the BBB during migraine attacks could be responsible for a possible central effect of sumatriptan in migraine. This review suggests that there is no need for a breakdown in the BBB to occur in order to explain a possible central CNS effect of sumatriptan.